Thai Students’ Satisfaction with Academic Services at Universities - Supriadi Supriadi; Widya Syafitri; Muhammad Kosim; Aldri Aldri (Institut Agama Islam Negeri Imam Bonjol Padang, 2025)
This study investigates the satisfaction levels of Thai students from Pattani enrolled in four public universities in West Sumatra, Indonesia. Using a quantitative descriptive method, the research evaluates perceptions of academic service quality across five key dimensions: tangibles, reliability, empathy, responsiveness, and assurance. Data were collected from all 29 Thai students actively enrolled at Andalas University, UIN Padang, UIN Batusangkar, and UIN Bukittinggi through an online Likert-scale questionnaire. The findings reveal overall high satisfaction levels, with variations across institutions: Andalas University scored the highest (4.14), followed by UIN Bukittinggi (3.98), UIN Padang (3.97), and UIN Batusangkar (3.74). While most students expressed positive perceptions, areas such as service convenience, speed, and infrastructure emerged as needing improvement. The study highlights the importance of continuous service evaluation and culturally responsive practices to enhance the academic experiences of international students in Indonesian higher education institutions.